Hippocampal-cerebellar involvement in enhancement of performance in word-based BRT with the presence of background noise: an initial fMRI study - Manan,Hanani Abdul (2012)
Background noise may impose deleterious effects on cognitive processing. However, noise below the threshold level may increase the ability to detect stimuli via stochastic resonance mechanisms (SR). The present study investigates whether task performance is deteriorated or enhanced by 5-dB SNR and, if the task performance is enhanced, whether this facilitation in performance points to a particular neural area that serves to attenuate noise and/or increase effective task performance. The areas of interest are the cerebellum and hippocampus due to their roles in working memory (WM) and their links with attention. Fifteen healthy young Malay adults performed three tasks during fMRI scanning: listening to babble noise (N), WM task in quiet (WMQ), and WM task in noise (WMN). Activated regions during N are bilateral STG and MTG. Both WM tasks produced similar activation in a network of areas in the frontal, temporal and parietal lobes. However, the two tasks demonstrated marked differences in the left hippocampus, right posterior cerebellum, and bilateral anterior cerebellum. Moreover, the results obtained from the behavioral task demonstrated that participants responded better in the presence of noise. These results support the hypothesis that the left hippocampus, right posterior cerebellum, and bilateral anterior cerebellum may be involved in attenuating noise and/or increasing attention to task performance, which could be due to SR mechanisms operating in the presence of noise. These results collectively suggest leftward asymmetries during the tasks with the right posterior cerebellum, bilateral anterior cerebellum, and left hippocampus providing compensatory attention processes, at least in the context of this study.